Analysis of oxide scale deformation and surface roughness characterisation in hot rolling of stainless steels. (2017) - Cheng, Xiawei; Wei, Dongbin; Jiang, Zhengyi; Jiang, Laizhu
Stainless steels are iron-based alloys that contain a minimum of about 12% Cr. They have been classified by microstructure at room temperature. Two stainless steel grades 304 and 410L were studied in this paper. Hot rolling was performed on a Hille 100 experimental rolling mill under various reductions with consideration of the oxide scale thickness controlled by oxidation time. The experimental results show that the deformation behaviour of the oxide scale on the stainless steel 304 is sensitive to its thickness and exhibits higher resistance to be deformed. However, the reduction in thickness plays an important role in the uniformity of the oxide scale deformation for the stainless steel 410L. Friction coefficients were calculated and compared. Simulations results show that the reduction in thickness and initial surface roughness play roles on final surface roughness. Steel substrate surface is rougher than that of the oxide scale at different reductions.